2012
DOI: 10.1111/j.1524-4725.2012.02577.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Expertise in Cutaneous Surgery and Cosmetic Procedures: What Primary Care Physicians Think

Abstract: Dermatologists are recognized as the most qualified specialist to perform a variety of cutaneous cosmetic and surgical procedures, including skin cancer surgery, botulinum toxin injections, filler injections, and laser procedures. Mohs fellowship-trained dermatologists were viewed as more qualified to perform MMS than other dermatologists, plastic surgeons, otolaryngologists, or ophthalmologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 15 publications
(26 reference statements)
0
26
0
Order By: Relevance
“…7 A 2012 survey of 561 primary care physicians identified dermatologists as the most qualified specialists to inject botulinum toxin and fillers and to perform laser procedures. 8 To continue as innovators and leaders in the safe performance of cosmetic dermatology procedures, future dermatologists must be properly trained. Regardless of prevailing PD attitudes toward the value and necessity of cosmetic dermatology training, the results of this survey demonstrate that almost every program provides hands-on cosmetic dermatology training during dermatology residency.…”
Section: Discussionmentioning
confidence: 99%
“…7 A 2012 survey of 561 primary care physicians identified dermatologists as the most qualified specialists to inject botulinum toxin and fillers and to perform laser procedures. 8 To continue as innovators and leaders in the safe performance of cosmetic dermatology procedures, future dermatologists must be properly trained. Regardless of prevailing PD attitudes toward the value and necessity of cosmetic dermatology training, the results of this survey demonstrate that almost every program provides hands-on cosmetic dermatology training during dermatology residency.…”
Section: Discussionmentioning
confidence: 99%
“…Recommendation We recommend that the health care provider should possess competence required to diagnose the patient's cutaneous vascular disorder, establish and explain his/her treatment needs, recognize and manage risks and deliver safe and appropriate laser/IPL treatment to remove or reduce vascular lesions in accordance with current standards of care and patient's expectations (GRADE 1C) …”
Section: Qualification Of Providers Of Laser And/or Ipl Treatmentmentioning
confidence: 99%
“…Substantial headway has been made in establishing the expertise of dermatologists within the medical community. For instance, a survey of 561 primary care physicians found that 56 % believe dermatologists to be the most qualified to perform surgery for skin cancer [17]. Significant strides have been made by the dermatology community to maintain perceptions such as these among fellow physicians.…”
Section: Discussionmentioning
confidence: 99%